Case teaching in economics: History, practice and evidence - Guglielmo Volpe (Cogent Economics & Finance, 2015)
Case studies are, normally, real-world problems that might include relevant or irrelevant data, correct or incorrect analysis and that require some sort of interpretation or solution. The use of case studies has been a common feature of undergraduate studies in business and law for a long time. In recent years, the so-called "case method" has become quite popular in economics education as well since it is believed to help the development to three key objectives in economics education: the mastering of economics principles, the application of principles to reality and the systematic analysis of policy issues. Coupled with student-centred approaches to learning, the case method can prove a very effective method in helping students to achieve a deeper understanding of both economic theory and policy analysis. The article provides an account of how case studies can be effectively used in economics teaching and reviews the empirical evidence on the effectiveness of the approach.
Keywords: 330; case method; newsclips; problem-based learning; student-centred approach; economic tools for teaching